PENGARUH PEMBERIAN REBUSAN BATANG BAJAKAH (Spathholobus littoralis Hassk) DENGAN PAPARAN ASAP ROKOK TERHADAP MORFOMETRI OVARIUM MENCIT (Mus musculus) - Ulfa, Setia Rana; Amaris, Bella Novita Susanto (Nusantara Hasana Journal, 2022)
Reproduction is the most important part of the life cycle. Many new cases are related to the reproductive organs caused by exposure to cigarette smoke. Pregnant women who are exposed to cigarette smoke can damage reproductive organs, such as the cervix, ovaries and fallopian tubes. The content of bajakah stems which contains a lot of antioxidants is thought to have an impact on reproductive health, especially in the ovaries, where the ovaries play an important role in the formation of egg cells. One of the plants that might be used is bajakah tampala, which contains flavonoids, tannins and saponins.